2018
DOI: 10.1051/matecconf/201818803007
|View full text |Cite
|
Sign up to set email alerts
|

Failure behavior of PA12 based SLS lattice structure with macro-porosity

Abstract: Abstract. Nowadays the demands of high reliability, high mechanical properties under fatigue loading and ultra-light-weight design are topics of pressing needs in different industry applications. Additive manufacturing technique has great potential to meet such demands and Selective Laser Sintering (SLS) is the dominantly used one due to its versatility in material design, construction and the much higher achievable mechanical strength compared to its competing technologies like fused filament fabrication. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Tables 2-4 describe the data based on the Tukey range test (looking at percentiles), including standard deviation values. The results illustrated in Figure 4 support the anisotropic behaviour of PA 12 reported earlier [13,23]. While the Tensile moduli for the XYZ and XZY orientations have similar distributions, the tensile modulus for the ZYX orientation has the widest variance and the lowest value.…”
Section: Description Of the Collected Datasupporting
confidence: 81%
See 2 more Smart Citations
“…Tables 2-4 describe the data based on the Tukey range test (looking at percentiles), including standard deviation values. The results illustrated in Figure 4 support the anisotropic behaviour of PA 12 reported earlier [13,23]. While the Tensile moduli for the XYZ and XZY orientations have similar distributions, the tensile modulus for the ZYX orientation has the widest variance and the lowest value.…”
Section: Description Of the Collected Datasupporting
confidence: 81%
“…A limited number of investigated features could be considered as another reason for such model performance. Since many studies have earlier reported that material properties have a significant impact on mechanical properties [3,13,18,23,41], and in this study they are not considered, this may have an impact on the obtained results.…”
Section: Prediction Of Tensile Modulus and Comparison Of Models' Perfmentioning
confidence: 95%
See 1 more Smart Citation
“…limited number of investigated features could be considered as another reason of such model performance. Since many studies have earlier reported that material properties has significant impact on mechanical properties[3,13,18,22,38], and in this study they are not considered, this may have an impact on the obtained results.However, prediction of Tensile Modulus based only on part positioning and STL model properties in ZYX orientation has promising results. Model based on the gradient boost regressor algorithm Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 5 March 2019 Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 5 March 2019 doi:10.20944/preprints201903.0051.v1…”
mentioning
confidence: 95%
“…Besides, Drummer et al [18] and Gümüs et al [22] studied how size of the parcticles of polymer powder and its viscosity influence mechanical properties. While Drummer et al [18] investigated degradation behavior of PA12 based on the analysis of phase transition temperature and melt viscosity for both virgin and aged powder, Gümüs et al [22] have reported that size of the particles and morphology could lead to the creation of pores, gaps or/and voids in the fabricated parts. The influence of part orientation on mechanical properties has already been described in the details by [12,23,24].…”
Section: Introductionmentioning
confidence: 99%